2022
DOI: 10.1161/jaha.122.025653
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and the Risk of Early‐Onset Dementia: A Systematic Review and Meta‐Analysis

Abstract: Background Recent studies have identified an increased risk of dementia in patients with atrial fibrillation (AF). However, both AF and dementia usually manifest late in life. Few studies have investigated this association in adults with early‐onset dementia. The aim of this study was to investigate the relationship between AF and early‐onset dementia. Methods and Results We searched the PubMed/MEDLINE, Embase, and Scopus databases through April 15, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…230 A third meta-analysis of 6 studies including ≈1.6 million individuals determined that the association of AF varied by age (RR, 1.06 [95% CI, 0.55–2.06] in those <65 years of age and RR, 1.50 [95% CI, 1.00–2.26] in those <70 years of age). 231…”
Section: Disorders Of Heart Rhythmmentioning
confidence: 99%
“…230 A third meta-analysis of 6 studies including ≈1.6 million individuals determined that the association of AF varied by age (RR, 1.06 [95% CI, 0.55–2.06] in those <65 years of age and RR, 1.50 [95% CI, 1.00–2.26] in those <70 years of age). 231…”
Section: Disorders Of Heart Rhythmmentioning
confidence: 99%
“…Average nighttime light intensity was more strongly associated with AD prevalence than some diseases and conditions reported or suspected to be risk factors for AD including alcohol abuse (Andrews, Goate, and Anstey 2020; Anstey, Mack, and Cherbuin 2009; Wang et al 2023; Nallapu et al 2023), chronic kidney disease (Zhang et al 2020; Tang et al 2022), depression (Saiz-Vazquez et al 2021), heart failure (Qiu et al 2006; Cermakova et al 2015), and obesity (Alford et al 2018; Al-Kuraishy et al 2023). However, other covariates were more strongly associated with AD than average nighttime light intensity including atrial fibrillation (Giannone et al 2022), diabetes, hyperlipidemia, hypertension, and stoke. This finding is perhaps not surprising as the effects of nighttime light exposure would be expected to be more subtle than factors robustly associated with AD.…”
Section: Discussionmentioning
confidence: 99%
“…It is of great concern the relatively higher risk of adverse effects in younger patients, including mortality and other mechanisms of increased risk of morbidity and mortality such as cognitive decline and dementia 2,9 . Of equal concern is that, despite improvements in awareness and detection of AF, improvements in therapies to lower risk of thromboembolism and the incidence and progression of coexistent cardiovascular diseases, and electronic medical support systems to improve use and understanding of clinical care pathways, a recent temporal analysis of the Framingham Heart Study over approximately 50 years found mortality rates have remained statistically similar since the 1970s (adjusted hazard ratios for all‐cause mortality between participants with and without AF were 1.9 (95% confidence interval: 1.7–2.2) in time period 1, 1.4 (1.3–1.6) in period 2, and 1.7 (1.5–2.0) in period 3 (Ptrend = 0.70) 10 .…”
Section: Af As a Contributor Of Multiorgan Adverse Outcomesmentioning
confidence: 99%